The attitude of Distance Learners towards the Utilization of Learning Management System (A case study of National Open University of Nigeria) - Ajijola, Esther M; Ogunlade, Oyeronke Olufunmilola; Aladesusi, Gboyega Ayodeji (Indonesian Journal of Teaching in Science, 2021)
One significant innovative technology to expand teaching and learning mostly in Distance Education is Learning Management System (LMS). LMS allow learning institutions to offer a larger number of courses online whether full or blended, by providing institutions with a digital space for numerous purpose which includes documentation, tracking and online training. However, for the relevance of LMS within an education context, distance learners’ attitudes towards the use of LMS must be investigated. The study therefore aimed at examining the Attitude of Distance Learners towards the Utilization of LMS (A case study of the National Open University of Nigeria). Data were collected from 697 respondents using a research adapted questionnaire. Data collected for the study were analyzed using mean and standard deviation to answer research question one while hypotheses one and two were tested using independent t-test and ANOVA respectively. The findings indicated that there was a significant difference between male and female distance learners on their attitude toward the use of LMS. Thus, no significant difference existed among science, arts, and social science distance learners’ attitude towards the use of LMS. It was therefore recommended that efforts should be made to ensure that distance learners do not just have a positive attitude towards the use of LMS but should be taught the value of LMS to ensure its effective utilization.